Womenpreneurs : 21st century success strategies - Moore, Dorothy P. (Routledge, 2012)
"WomenPreneurs: 21st Century Success Strategies, will appeal to three groups of interested readers. The first consists of higher education faculty teaching courses in management, entrepreneurship and women's studies and directors of professional development workshops interested in acquiring a supplemental readings book. The second consists of women in the workplace, those contemplating entry, parents who want to provide daughters with the best guidance as well as men and significant others who want those they love to have a safer navigational journey and recognize that the work environment they will enter is not a level playing field. The third group includes intrapreneurial and entrepreneurial women in all stages of personal and venture development. For these people, the book will serve as a valuable resource and guide. Major themes in the book include the nature of the changing workplace, the challenges of organizational life, career strategies, entrepreneurship, home and family balance and tactics for navigating in a turbulent economic climate." -- Publisher's website